Proposed Solutions to Vaccine Storing and Distribution at PT. POS Logistik Indonesia, Bandung - Vina Dwiyanti; Davin Arkan Admoko Putra; Ahmad Reza Ar-rafi; Anim Muslim (Universitas Pendidikan Indonesia, 2023)
This case study digs into the involvement of students in the logistic engineering curriculum at Universitas Pendidikan Indonesia in real-world logistics problems. The research is based on a consulting project carried out in partnership with PT. POS Logistik Indonesia, is a well-known logistics company specializing in health and vaccine product warehousing. The primary responsibility allocated to the students is to meticulously observe, thoroughly analyze, and provide solutions for material handling procedures within the boundaries of the company's warehouse facilities. While the main goal was to collect visual documentation of the warehouse, PT. POS Logistik Indonesia delivered Standard Operating Procedure (SOP) documents relevant to health and vaccine product management. This made it possible to approach the consultation assignment in a more collaborative and informed manner. The primary goal of this article is to identify relevant difficulties and formulate prescriptive solutions based on interviews and on-site visits, with a particular emphasis on the improvement of vaccine storage and handling techniques to avoid waste in future initiatives.